2017
DOI: 10.1038/srep44714
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition of deep-sea corals from the Red Sea provides insight into functional adaption to a unique environment

Abstract: Microbes associated with deep-sea corals remain poorly studied. The lack of symbiotic algae suggests that associated microbes may play a fundamental role in maintaining a viable coral host via acquisition and recycling of nutrients. Here we employed 16 S rRNA gene sequencing to study bacterial communities of three deep-sea scleractinian corals from the Red Sea, Dendrophyllia sp., Eguchipsammia fistula, and Rhizotrochus typus. We found diverse, species-specific microbiomes, distinct from the surrounding seawate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…The deep Red Sea with low oxygen (1-2 mg O 2 L −1 ) and limited nutrient availability due to warm temperatures (>20 • C) features markedly different conditions than otherwise common for deep-sea coral habitats . In line with other studies, Röthig et al (2017) showed that these coral microbiomes were species-specific and suggested functional adaptation to their environment. These adaptations include in particular the presence of anaerobe bacterial taxa and potential hydrocarbon degraders.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…The deep Red Sea with low oxygen (1-2 mg O 2 L −1 ) and limited nutrient availability due to warm temperatures (>20 • C) features markedly different conditions than otherwise common for deep-sea coral habitats . In line with other studies, Röthig et al (2017) showed that these coral microbiomes were species-specific and suggested functional adaptation to their environment. These adaptations include in particular the presence of anaerobe bacterial taxa and potential hydrocarbon degraders.…”
Section: Introductionsupporting
confidence: 74%
“…About 90 min later upon retrieval, samples were rinsed with sterile-filtered seawater, crushed on liquid nitrogen, and stored at −80 • C. To assess the in situ microbiome 3 of the 4 E. fistula samples described in Röthig et al (2017) were used in this study. To ensure an evenly distributed sample set and a high sequencing depth, one in situ sample from Röthig et al (2017) presenting the lowest coverage was disregarded. Further, a water sample from the corals' direct vicinity was taken using Niskin bottles.…”
Section: Coral Collection and Rearingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, transplantation of corals to a warmer environment resulted in shifts in the associated bacterial community that correlated with increased holobiont thermotolerance 87 . Additionally, higher bacterial diversity in deep compared to shallow water corals 88,89 suggests that some deep habitat-specific microbes may be involved in nutrient cycling specific to the low-irradiance environments. Both genetic and epigenetic processes contribute to high phenotypic plasticity and rapid evolution in bacteria 90 .…”
Section: Potential Involvement Of Microbes In Coral Acclimatizationmentioning
confidence: 99%